2015
DOI: 10.7863/ultra.34.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Precision of Stress Sonography of the Ulnar Collateral Ligament

Abstract: Medial elbow stress sonography is a reliable and precise method for detecting changes in ulnohumeral joint gapping and UCL lengthening. Ultimately, this method may provide clinicians valuable information regarding the medial elbow's response to valgus loading and may help guide treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…8,20,28 In addition, Bica et al showed that medial elbow stress sonography is a reliable and precise method for detecting changes in ulnohumeral joint space gapping. 6 In addition, we compared medial elbow joint space gapping before and after 100 pitches in the throwers with and without an elbow brace in 2017. 20 In that crossover design study with 1 week washout period, there was no significant difference in medial elbow joint space gapping before pitching in the 2 groups, and it is clear that medial elbow joint space gapping increases as the number of throws increase.…”
Section: Resultsmentioning
confidence: 99%
“…8,20,28 In addition, Bica et al showed that medial elbow stress sonography is a reliable and precise method for detecting changes in ulnohumeral joint space gapping. 6 In addition, we compared medial elbow joint space gapping before and after 100 pitches in the throwers with and without an elbow brace in 2017. 20 In that crossover design study with 1 week washout period, there was no significant difference in medial elbow joint space gapping before pitching in the 2 groups, and it is clear that medial elbow joint space gapping increases as the number of throws increase.…”
Section: Resultsmentioning
confidence: 99%
“…Although further studies are necessary to standardize and test these 4 diagnostic steps, their proposed use is feasible. Ultrasound machines are available in most emergency departments and orthopedic offices and, with the proper training, can be used to examine potential Lisfranc injuries . This would be beneficial to both the patient and physician: quick visualization of the ligament promotes rapid treatment, and the patient does not need to bear weight on an injured joint complex for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increase in the width of the medial joint space of the dominant arm. 1,2,14 Our study chose to use the nondominant arms of those who were not overhead throwing athletes. Using these participants ensured that the differences found in this study were not due to anatomic adaptations associated with repeated valgus loading but, rather, anatomic changes associated with changes in the flexion angle.…”
Section: Discussionmentioning
confidence: 99%